Accelerating technical change through video mediated agricultural extension - Abate, Gashaw T.; Fayso, Tadele (CGIAR System Organization, 2019)
Agricultural extension is crucial for promoting equality of opportunity among smallholders. Ethiopia has one of Africa’s largest extension systems: 1) 17.5 million smallholder farmers 2) 1 extension agent per 400-500 farmers.